The Role of Amnioreduction in Emergency Cervical Cerclage with Bulging Membranes: A Retrospective Comparative Study - Zhang, Yuan; Wang, Qingqing; Tan, Zhangmin; Zhou, Jin; Zhang, Peizhen; Hou, Hongying; Yin, Yuzhu; Han, Zhenyan (Frontiers in Surgery, 2022)
The purpose of this study was to investigate the role of amnioreduction in patients who underwent emergency cervical cerclage (ECC) with bulging membranes during the second trimester. This retrospective comparative study included 46 singleton pregnant women who had cervical dilation at least 1 cm with bulging membranes beyond the external cervical os and underwent ECC at the Third Affiliated Hospital of Sun Yat-sen University between December 2016 and December 2021. Cases were categorized as amnioreduction group (n = 16) and non-amnioreduction group (n = 30) according to whether amnioreduction was performed prior to ECC. The gestational age and cervical dilation at cerclage, operative time, prolongation of pregnancy, and outcomes of pregnancy were compared between the two groups. All 46 patients underwent successful ECC excepted one case with intraoperative rupture of membrane in non-amnioreduction group. In the amnioreduction group, the cervical dilation at cerclage was larger than that in the non-amnioreduction group (4.5 ± 2.2 vs. 2.2 ± 1.2 cm, P < 0.001), and had more patients with cervical dilation ≥ 4 cm (50.0% vs. 10.0%, P = 0.004). However, the gestational age at cerclage, operative time, prolongation of pregnancy, gestational age at delivery were not significantly different between the two groups (22.9 ± 2.8 vs. 22.9 ± 3.2 weeks, 31.1 ± 9.2 vs. 27.9 ± 11.4 minutes, 21.3 ± 21.5 vs. 38.7 ± 40.2 days, 25.9 ± 4.5 vs. 28.4 ± 6.1 weeks; P > 0.05). The rates of delivery ≥ 28 weeks, ≥ 32 weeks, and live birth were 20.0% vs. 80.0%, 12.5% vs. 26.7%, 56.3% vs. 66.7% (P > 0.05) in amnioreduction group and non-amnioreduction group, respectively. In conclusion, even in cases with larger cervical dilation, application of amnioreduction with ECC is possible to get the acceptable pregnancy outcomes. These findings suggested that amnioreduction may be a safe and feasible option to be applied before ECC, especially for those with advanced cervical dilation and bulging membranes.